2019
DOI: 10.13189/iid.2019.070102
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV in a Cohort of Pregnant Women Attending a Tertiary Hospital in Ibadan, Nigeria

Abstract: HIV/AIDS is one of the major barriers to community development. It is a global pandemic with high prevalence rates worldwide. This research was carried out to determine the prevalence of HIV among pregnant women attending the antenatal clinic at the University College Hospital, Ibadan using Enzyme Linked Immunosorbent Assay (ELISA) Gen Screen TM ULTRA HIV Ag-Ab Kit. HIV prevalence was found to be 26.4%. A total of 91 samples were tested, 24 (26.4%) were found to be positive and 67 (73.6%) negative. Women betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…However, the 3.5% prevalence of HIV infection among pregnant women in this study is still high than the Nigerian national prevalence of 1.4% [36]. The prevalence of the infection from other previous studies done in Nigeria among pregnant women has also been quite high and range from 4.0% in Damaturu [3], to 8.3% in Jos [37] and 26.4% in Ibadan [38]. This therefore calls for more intervention programs for the control and prevention of this viral infection particularly among pregnant women due to its devastating medical implications not only to them but also to their unborn child.…”
Section: Limitationscontrasting
confidence: 49%
“…However, the 3.5% prevalence of HIV infection among pregnant women in this study is still high than the Nigerian national prevalence of 1.4% [36]. The prevalence of the infection from other previous studies done in Nigeria among pregnant women has also been quite high and range from 4.0% in Damaturu [3], to 8.3% in Jos [37] and 26.4% in Ibadan [38]. This therefore calls for more intervention programs for the control and prevention of this viral infection particularly among pregnant women due to its devastating medical implications not only to them but also to their unborn child.…”
Section: Limitationscontrasting
confidence: 49%
“…In 2015, the Nigerian government reported that over 177, 993 pregnant women were living with HIV in Nigeria, and the figures were likely to rise in the coming years (NACA Fact Sheet, 2016 ). Further, the prevalence of HIV/AIDS among pregnant women in Nigeria has been estimated to be over 26.4%, and this is higher than most other sub‐Saharan African countries (Mbachu et al, 2020 ; Okonko, Osadebe, Onianwa, & Okereke, 2019 ). Hence, conducting the current study on the target population in Nigeria is a timely action.…”
Section: Introductionmentioning
confidence: 96%
“…It is shown worldwide statistically that 15% of HIV positive females fall within the group of 15 -24 years. Okonko et al [39] showed that the greatest occurrence was found among persons of 25-31years. Furthermore, some studies showed the dominance of females within the age bracket of 20 -29 years [40,41].…”
Section: Discussionmentioning
confidence: 97%